2017
DOI: 10.29252/ijal.20.1.1
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Iranian EFL University Learners’ Creative Thinking and Critical Thinking Skills in a Pedagogical Blog: A Mixed-Methods Approach

Abstract: The present study explored the effect of a pedagogical blog on Iranian EFL learners' creative and critical thinking skills using a mixed-methods approach. In the pedagogical blog, the researchers asked learners divergent and evaluative questions based on Lindley's model (1993). The quantitative data were collected by administering Creativity Test Questionnaire (ATC) and the Persian version of the California Critical Thinking Skills Test and were analyzed using SPSS Version 16.0 software. The qualitative data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…They have been selected from three Iraqi Universities: University of Kufa, Al-Hilla University College, Al-Sadeq University in Baghdad and Najaf. Table (1) below provides the main profile of the respondents. The teachers' consent to participate in the study was sought and secured.…”
Section: Methodology Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been selected from three Iraqi Universities: University of Kufa, Al-Hilla University College, Al-Sadeq University in Baghdad and Najaf. Table (1) below provides the main profile of the respondents. The teachers' consent to participate in the study was sought and secured.…”
Section: Methodology Participantsmentioning
confidence: 99%
“…Pragmatic awareness refers to the learners' consciousness of the significance of the sociopragmatic aspects in their use of L2 (Chavarria & Bonany, 2006, p. 141). Similarly, other researchers assert that knowing pragmatic aspects such as speech acts, pragmalinguistics, strategic moves, and politeness principles plays a crucial role in the process of L2 development (Yates, 2004;Adel et al, 2016). Cohen (2010) stresses the role of pragmatic awareness in language learning since it enhances the learners' attention to the interactive strategies of communication in a variety of academic and sociocultural contexts.…”
Section: Pragmatic Awarenessmentioning
confidence: 99%
“…Politeness is the way speaker appreciating and maintaining the situation to the hearer in the interaction (Manik & Hutagaol, 2015;Widodo & Al Muchtar, 2020). Politeness is can be said as the implementation of good manner in daily life (Adel et al, 2016;Manik & Hutagaol, 2015;Sihite et al, 2021). Being polite is complicated but sometimes interesting thing in any language.…”
Section: Introductionmentioning
confidence: 99%
“…With the world moving rapidly into digital media and information, the role of ICT in education is becoming more and more important (Qazi et al, 2021;Swindell & Wright, 2022). It has been suggested that information and communication technologies (ICTs) can and play a number of roles in education such as developing the kind of graduates and citizens required in an information society; improving educational outcomes and enhancing and improving the quality of teaching and learning (Adel et al, 2016;Moustakas & Robrade, 2022).…”
Section: Introductionmentioning
confidence: 99%